2000
DOI: 10.1208/ps020101
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of nevirapine and lamivudine in patients with HIV-1 infection

Abstract: The purpose of this parallel treatment group, double-blind, multicenter study was to characterize the pharmacokinetics of nevirapine and lamivudine when coadministered to patients with the HIV -1 infection. This pharmacokinetic interaction study was nested within a larger Phase III clinical trial conducted to characterize the safety and efficacy of coadministered nevirapine and lamivudine. One hundred HIV -1 infected patients with CD4+ lymphocyte counts = 200 cells/mm 3 and who were on a background of) therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
17
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 14 publications
2
17
0
1
Order By: Relevance
“…The estimates from the final population pharmacokinetic model of CL/F, V/F and k a are consistent with previous reports of nevirapine population pharmacokinetics in other populations [24][25][26]. In our study, rifampicin induced the metabolism of nevirapine, seen as an increase in its CL/F by 37.4%, which is in agreement with previous reports of rifampicin altering the pharmacokinetics of nevirapine [4,9,10,12,13].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The estimates from the final population pharmacokinetic model of CL/F, V/F and k a are consistent with previous reports of nevirapine population pharmacokinetics in other populations [24][25][26]. In our study, rifampicin induced the metabolism of nevirapine, seen as an increase in its CL/F by 37.4%, which is in agreement with previous reports of rifampicin altering the pharmacokinetics of nevirapine [4,9,10,12,13].…”
Section: Discussionsupporting
confidence: 92%
“…Weight was therefore not included in the final model as a predictor of variability in CL/F. A lack of relationship between weight and nevirapine pharmacokinetics has also been seen in other studies [13,24,26,43]. Age was also found to be a predictor of variability in CL/F, where CL/F increased by 1.56% with every 1-year increase in age relative to the population median age of 34.6 years.…”
Section: Discussionmentioning
confidence: 78%
“…Interestingly, the effect of nevirapine induction on CYP2B6 activity leads to an increased concentration of 3-hydroxynevirapine and a lower concentration of the 2-hydroxynevirapine metabolite formed through the CYP3A pathway. The pharmacokinetic characteristics of parent nevirapine in the present study agree with those of previous studies conducted in patients or volunteers after a single dose or at steady state, a finding which clearly demonstrates the autoinducing properties of nevirapine (10,(19)(20)(21)(22)(23)(24)(25)(26)(27). Indeed, the two populations studied herein differ by their ethnicity, demographics, and HIV infection status; the CYP2B6 *1*6 genetic polymorphism frequency is very close, but the significant difference remains when clearances are weight normalized (0.83 ml/ min/kg versus 0.29 ml/min/kg).…”
Section: Discussionsupporting
confidence: 91%
“…A previous study with lamivudine in the IPK model showed that the renal excretion of this agent was reduced in the presence of trimethoprim (Sweeney et al, 1995), and subsequent clinical trials confirmed that this interaction might be clinically relevant (Moore et al, 1996;Sabo et al, 2002), although no dose adjustment is recommended (Epivir SmPC). Given the structural similarities between ATC and lamivudine, it is possible that ATC might be subject to a similar interaction with trimethoprim.…”
mentioning
confidence: 99%